THE IMPACT OF E-WOM QUANTITY AND E-WOM CREDIBILITY ON ONLINE PURCHASE INTENTIONS FOR GARNIER WITH BRAND IMAGE AS A MEDIATING FACTOR - Surya, Dominic Kenji Kurnia; Utama, Louis (International Journal of Application on Economics and Business, 2025)
This study looks at how brand image mediates the relationship between e-WOM quantity and e-WOM purchase ability and online purchase intentions. This study, which includes 160 samples, focuses on Garnier product users in Jakarta. Researchers used SmartPLS4 software to evaluate data obtained via a questionnaire instrument (G-form). The study's findings indicate that online purchase intentions for Garnier goods in Jakarta are positively impacted by e-WOM quantity, e-WOM legitimacy, and brand image. Using Garnier goods in Jakarta, this study examines how brand image influences online purchase intentions by balancing e-WOM credibility and quantity. shows how crucial it is for businesses, particularly Garnier, to boost the volume and legitimacy of e-WOM and improve brand perception in order to stimulate online customer purchase intentions. In order to draw in more customers and increase sales on bold platforms, businesses should concentrate their efforts on enhancing the caliber of reviews and bolstering brand image through efficient marketing techniques. Apart from that, companies also need to consider managing their online reputation on an ongoing basis to remain competitive in a competitive market.